2009
DOI: 10.1246/cl.2009.174
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 4-Thiopseudoisocytidine and 4-Thiopseudouridine as Components of Triplex-forming Oligonucleotides

Abstract: In this paper, we report convenient methods for the synthesis of 4-thiopseudoisocytidine (s 4 iC) and 4-thiopseudouridine (s 4 É). 1 H NMR spectral analysis of these modified nucleosides showed that both s 4 É and s 4 iC prefer C3 0 -endo ribose puckering. These conformational properties are favorable for the stabilization of triplex formation.Using the antigene strategy, a large number of modified nucleosides have been synthesized to enhance the thermal stability of DNA triplexes formed by hybridization of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Simulations with the application of the AMBER FF99 parameters for the modified residues in combination with the revised γ torsion parameters and the revised χ torsional parameters developed earlier in our lab generated conformations, which were in better agreement with the available experimental (NMR) data , compared to those generated by simulations with the default AMBER parameters for each of the modified nucleosides (Figures – and Tables S6–S8). Overall, the observations were quite similar to those for Ψ.…”
Section: Results and Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Simulations with the application of the AMBER FF99 parameters for the modified residues in combination with the revised γ torsion parameters and the revised χ torsional parameters developed earlier in our lab generated conformations, which were in better agreement with the available experimental (NMR) data , compared to those generated by simulations with the default AMBER parameters for each of the modified nucleosides (Figures – and Tables S6–S8). Overall, the observations were quite similar to those for Ψ.…”
Section: Results and Discussionmentioning
confidence: 55%
“…The results obtained from three independent sets of 16 ns REMD simulations using the FF99 parameters, FF99_bsc0 parameters, , FF99_χ IDRP parameters, , and FF99_χ IDRP _bsc0 parameters, ,, were compared to the available experimental (NMR) data , for the m 1 Ψ, m 3 Ψ, Ψm, and m 1 acp 3 Ψ residues.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[104] Prompted by prior studies that indicated that triple-stranded RNAs prefer an A-form conformation, [105][106][107] Sekine and coworkers found that s2U bases in triplex forming oligos (TFOs) could also bind AU sites in dsRNA to form triplexes; [108] they subsequently exploited the enhanced stacking of the thione substitution with 4-thiopseudoisocytidine (s 4 ΨiC) bases in TFOs to target GC base pairs in dsRNAs. [109,110] The Chen lab later demonstrated that both s2U and s 4 ΨiC could also target AU and GC pairs in dsRNA when the thio bases are presented on a PNA backbone, driven only by gains in base stacking and hydrogen-bonding in the absence of a sugar backbone. [15,111,112]…”
Section: Native Cytidine and Uridine Derivatives That Stabilize Trimentioning
confidence: 99%
“…The MD and REMD results with the FF99, FF99χ_YIL, and FF10 force fields showed almost no difference in the population of NORTH and SOUTH conformations and were very much consistent with NMR results for PSU 73,74 (Table 2, Figure 2A, Figure 2B, Figure 2D and Figure S1A, Figure S1B, Figure S1D, Supporting Information). However, simulations with the FF99TOR force field showed a slight shift toward the SOUTH conformation (Table 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%